2020
DOI: 10.3390/w12092635
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Surface Water and Groundwater in Yinchuan Plain

Abstract: The interaction of surface water (SW) and groundwater (GW) is becoming more and more complex under the effects of climate change and human activity. It is of great significance to fully understand the characteristics of regional SW–GW circulation to reveal the water circulation system and the effect of its evolution mechanism to improve the rational allocation of water resources, especially in arid and semi-arid areas. In this paper, Yinchuan Plain is selected as the study area, where the SW–GW interaction is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 61 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…Meanwhile, the vertical infiltration of agricultural irrigation water promotes the leaching and dissolution of mineral and soil salt, which could thus transfer the soluble salt downward into phreatic water, causing the higher salinity of groundwater in summer (Figure 11) [48]. Previous studies reported that evaporites and saline soil were widespread in the irrigated district of the Tarim Basin, due to the irrational irrigation, inefficient drainage, and violent surface evaporation [15,33]. Wang et al found that groundwater salinity was significantly correlated to soil salinity in saline-alkaline land in an arid oasis [14].…”
Section: Impacts Of Land Use Change On Groundwater Hydrochemistrymentioning
confidence: 98%
See 4 more Smart Citations
“…Meanwhile, the vertical infiltration of agricultural irrigation water promotes the leaching and dissolution of mineral and soil salt, which could thus transfer the soluble salt downward into phreatic water, causing the higher salinity of groundwater in summer (Figure 11) [48]. Previous studies reported that evaporites and saline soil were widespread in the irrigated district of the Tarim Basin, due to the irrational irrigation, inefficient drainage, and violent surface evaporation [15,33]. Wang et al found that groundwater salinity was significantly correlated to soil salinity in saline-alkaline land in an arid oasis [14].…”
Section: Impacts Of Land Use Change On Groundwater Hydrochemistrymentioning
confidence: 98%
“…The cultivated land area has markedly expanded from 2000 to 2020 (increasing by 732.38 km 2 (121.8%)) in the study region (Table 1 and Figure 4), and agricultural irrigation relies on stream water and pimped groundwater, thus leading to irrigation return flow as a dominant source of phreatic water [16]. That is, agricultural irrigation and groundwater extraction play an important role in the seasonal change of groundwater quantity and quality [15,27]. For the cultivated land, the vertical infiltration of irrigation water could cause the groundwater level to rise, but groundwater extraction leads to groundwater level decline in the growing season (Figure 11).…”
Section: Impacts Of Land Use Change On Groundwater Hydrochemistrymentioning
confidence: 99%
See 3 more Smart Citations